2021
DOI: 10.3390/met11020256
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Electrochemical and Morphological Investigation on the Behavior of NiCr and CoCr Dental Alloys at Various Temperatures

Abstract: The purpose of our study is to compare the behavior of two reprocessed dental alloys (NiCr and CoCr) at different temperatures considering the idea that food and drinks in the oral cavity create various compositions at different pH levels; the novelty is the investigation of temperature effect on corrosion parameters and ion release of dental alloys. Electrochemical stability was studied together with morphology, elemental composition and ions release determination. The results obtained are in good concordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…With the high concern about chromium and cobalt [7,8,13,16], in this study, we intend to investigate the interaction between the following metal ions and saccharides frequently used in the pharmaceutical industry: cyclodextrins and hyaluronic acid. It should be stressed that metal salt solutions were used in previous studies of cytotoxicity of dental alloys, as reported elsewhere [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…With the high concern about chromium and cobalt [7,8,13,16], in this study, we intend to investigate the interaction between the following metal ions and saccharides frequently used in the pharmaceutical industry: cyclodextrins and hyaluronic acid. It should be stressed that metal salt solutions were used in previous studies of cytotoxicity of dental alloys, as reported elsewhere [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The oral cavity has specific and individualized characteristics, with a wide variety of pH, bacterial load, and temperature variation [ 1 , 2 ]. Temperature and pH of the oral cavity and fluids are two significant factors that affect the electrochemical behavior of restorative dental materials used in a correct dental treatment plan [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%